Systematic review of body image measures. (September 2019) - Kling, Johanna; Kwakkenbos, Linda; Diedrichs, Phillippa C.; Rumsey, Nichola; Frisén, Ann; Brandão, Maria Piedade; Silva, Anabela G.; Dooley, Barbara; Rodgers, Rachel F.; Fitzgerald, Amanda
Highlights: There are psychometrically sound measures to assess evaluative body image. Suitability of these body image measures vary across populations. Some measurement properties of body image measures are insufficiently studied. More evaluations are needed across populations, focusing on cross-cultural validity. More evaluations of body image measures in clinical settings are needed. Abstract: This systematic review synthesizes and critically appraises measurement properties of influential body image measures. Eight measures that met the definition of an assessment of body image (i.e., an individual's cognitive or affective evaluation of their body or appearance with a positive or negative valence), and scored high on systematic expert priority ranking, were included. These measures were: the Body Appreciation Scale (original BAS and BAS-2), the Body Esteem Scale for Adolescents and Adults, the Body Shape Questionnaire, the Centre for Appearance Research Valence Scale, the Drive for Muscularity Scale, two subscales of the Eating Disorders Examination Questionnaire, one subscale of the Eating Disorder Inventory 3, and two subscales of the Multidimensional Body Relations Questionnaire. Articles assessing these scales' psychometric properties ( N = 136) were evaluated for their methodological quality using the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) checklist, and a best evidence synthesis was performed. The results supported the majority of measures in terms of reliability and validity; however, suitability varied across populations, and some measurement properties were insufficiently evaluated. The measures are discussed in detail, including recommendations for their future use in research and clinical practice.